Metformin Downregulates PD-L1 Expression in Esophageal Squamous Cell Carcinoma by Inhibiting IL-6 Signaling Pathway - Yao Lu; Dao Xin; Lulu Guan; Mengli Xu; Yalan Yang; Yu Chen; Yuanyuan Yang; Andrea Wang-Gillam; Li Wang; Shanggang Zong; Feng Wang (Frontiers in Oncology, 2021)
PurposeTo characterize the mechanism by which metformin inhibits PD-L1 expression in esophageal squamous cell carcinoma (ESCC) and to evaluate the effect of metformin on the antitumor immune response.MethodsThe Cancer Genome Atlas (TCGA) database was used to analyze the correlations between IL-6 and prognosis and between IL-6 and PD-L1 gene expression in esophageal cancer. Reverse transcription-quantitative polymerase chain reaction (RT-PCR), Western blotting and immunofluorescence were used to study the mechanism by which metformin affects PD-L1 expression. Additionally, T cell function was assessed in a coculture system containing ESCC cells and peripheral blood mononuclear cells (PBMCs) treated with metformin or IL-6. In an in vivo assay, we used a model established with NPIdKO™ mice, which have a reconstituted immune system generated by transplanting PBMCs through intravenous injection, to evaluate the effect of metformin on tumors.ResultsThe TCGA esophageal cancer data showed that IL-6 expression was positively correlated with PD-L1 expression and that patients with high IL-6 expression had a significantly lower overall survival rate than patients with low IL-6 expression. PD-L1 expression in ESCC cell lines was significantly inhibited by metformin via the IL-6/JAK2/STAT3 signaling pathway but was not correlated with the canonical AMPK pathway. In the coculture system, the metformin pretreatment group showed higher T cell activation and better T cell killing function than the control group. Animal experiments confirmed that metformin downregulated PD-L1 expression and that combination treatment with metformin and PD-1 inhibitors synergistically enhanced the antitumor response.ConclusionsMetformin downregulated PD-L1 expression by blocking the IL-6/JAK2/STAT3 signaling pathway in ESCC, which enhanced the antitumor immune response.